Assessing the needs for Javanese learning for speakers of other languages - Ekowati, Venny Indria; Sugiarto, Tri; Nooryastuti, Nandyan Ayu; Nurhayati, Endang; Wulan, Sri Hertanti (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
This article presents a report on the needs analysis of Javanese learning for speakers of other languages. Applying the descriptive-analytical method, this study used data gathered from the survey of 57 participants from 27 different countries. The present study revealed that the most difficult aspect of studying Javanese is on mastering its vocabulary (54.8%). This condition limited the learners' confidence to engage in any conversation with the locals (74.2%) and made them less progressive in some other related competencies such as reading and writing. Based on the participants' responses to the survey, the approach recommended to facilitate the program of Javanese for speakers of other languages is the communicative approach. The design of the program targeted proficiency in communicating using Javanese. Vocabulary learning is needed in real situations and contexts. Therefore, the learners could improve their capacity in Javanese and engage with the local people better. Through its comprehensive examination of the challenges, opportunities, and potential solutions, this research not only contributes to the field of language education but also reinforces the value of embracing linguistic diversity as a cornerstone of our shared human experience.